Deacylative Carbon‐Carbon Bond Cleavage of Ketone Equivalents: Applications to Radical Carbon‐Carbon Bond Formation Reactions. Issue 4 (12th January 2021) - Matsumoto, Akira; Nguyen, Bich‐Ngoc; Honda, Tsubasa; Sakamoto, Ryu; Huang, Xiao; Sakaki, Shigeyoshi; Maruoka, Keiji
Abstract: This article describes the synthetic application of ketone‐derived oxaziridines as alkyl radical precursors in copper‐catalyzed Carbon‐Carbon bond formation reactions. Experimental and computational studies indicate a free radical mechanism, where alkyl radicals are efficiently generated via cleavage of a Carbon‐Carbon bond of oxaziridines. Acyclic and unstrained cyclic oxaziridines are applicable to the present radical process, allowing for the generation of various alkyl radicals with good functional group compatibility. Abstract : The synthetic application of ketone‐derived oxaziridines as alkyl radical precursors in copper‐catalyzed Carbon‐Carbon bond formation reactions is described. Experimental and computational studies indicate a free radical mechanism, where alkyl radicals are efficiently generated via cleavage of a Carbon‐Carbon bond of oxaziridines. Acyclic and unstrained cyclic oxaziridines are applicable to the present radical process, allowing for the generation of various alkyl radicals with good functional group compatibility.